LA EJECUCIÓN DE REMATES SOBRE BIENES SOCIALES AFECTADOS CON MEDIDA CAUTELAR DE EMBARGO POR DEUDA DE UNO DE LOS CÓNYUGES - Santos Stevens, Gutiérrez León (2018)
Thiswork deals with the problem that exists in cases in which precautionary measures on social assets are tied to private debts of one of the spouses, because, first of all, it is an assumption of fact not regulated, expressly, in our country, despite the fact that in everyday life there are many cases in which the interest for the protection of family’s economic is put in confrontation against the creditors' right to collect the outstanding credit. Given this, it is known that judges cannot stop administering justice due to deficiencies or gaps in the rules, that’s why two contradictory positions have been identified, in which one of them magistrates who do not grant the precautionary measures requested by the creditors, based on the social condition of the good to affect, and on the other hand, there are those who, although granting the aforementioned precautionary measures, such as the embargo, recognize that it cannot be enforced, becoming ineffective, by not fulfilling its guarantee purpose. In that sense, we have analyzed how this situation has been protected in the Superior Court of Justice of La Libertad, compiling some resolutions in which they grant such measure, and what is the procedure that is followed when its execution is requested. Likewise, we have gathered the opinions of the specialized civil magistrates, to identify what would be the response of this Court to the aforementioned precautionary requests, and if they, as legal operators, consider that these measures are an effective means to guarantee the right of the creditor, taking into account the current national regulations. Key Words: Patrimonial regime, community property system, privative debts, embargo.